Harmonites in 5-Point Protest Memo - Unknown (Daily Express)
The captain and a delegation from the disqualified steelband Solo Harmonites will send a five-point memorandum to the Carnival Development Committee. The memo will answer the case put forward by the executive of the Steelband Association for the disqualification. Solo Harmonites captain Joseph Renaud stressed that the stated penalty for not appearing in the proper order was a deduction of five points - no mention of disqualification was made.
Keywords: Steel bands (Music) -- Competitions -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago; Steel bands (Music) -- Administration -- Trinidad and Tobago